Essential Methods and Institutions of Supporting National Exports - Medukhanova, L. A. (Farabi Journal of Social Sciences, 2019)
In modern foreign trade policy of the country the important place is taken by system of the measures directed to support of national export. These measures include the various methods helping entry of exporters of domestic production into foreign markets. The article discusses the main financial and non-financial supporting for exports methods which developed by international practices and their application in Kazakhstan. For the Republic of Kazakhstan participating in the international specialization as the exporter of mineral resources, problems of development of the processing sectors of production and, accordingly, the growth of non-oil exports are relevant. The possibilities of the solution of these problems are considered on the example of use of methods of the state support of export in activities of the specialized organizations of Kazakhstan for assistance of export of the processed products. Key words: export, tariff and non-tariff regulation methods, financial methods, measures of non-financial support of exporters, non-oil export.